HLHS: Power of the Chick Model - David Sedmera (Journal of Cardiovascular Development and Disease, 2022)
Background: Hypoplastic left heart syndrome (HLHS) is a rare but deadly form of human congenital heart disease, most likely of diverse etiologies. Hemodynamic alterations such as those resulting from premature foramen ovale closure or aortic stenosis are among the possible pathways. Methods: The information gained from studies performed in the chick model of HLHS is reviewed. Altered hemodynamics leads to a decrease in myocyte proliferation causing hypoplasia of the left heart structures and their functional changes. Conclusions: Although the chick phenocopy of HLHS caused by left atrial ligation is certainly not representative of all the possible etiologies, it provides many useful hints regarding the plasticity of the genetically normal developing myocardium under altered hemodynamic loading leading to the HLHS phenotype, and even suggestions on some potential strategies for prenatal repair.